وراثة صفة الغلة الحبية ومكوناتها في الذرة الصفراء (Zea mays L. ) وفق طريقة سلالة × مختبر (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
أجري البحث في مركز البحوث الزراعية في الغاب، سورية خلال الموسمين الزراعيين 2013 و 2014 بهدف تقدير القدرة على الائتلاف وقوة الهجين والارتباط المظهري وتحليل المسار لصفات ارتفاع النبات والعرنوس، طول وقطر العرنوس، وعدد الصفوف بالعرنوس، وعدد الحبوب بالصف، ووزن المائة حبّة وغلّة النبات الفردي لثمانية عشر هجيناً فردياً ناتجة عن التهجين بطريقة سلالة في مختبر لست سلالات أبوية وثلاث سلالات مختبرة. أظهرت النتائج أن تباين السلالات والمختبرات والهجن كان معنوياً لجميع الصفات المدروسة، وأظهرت القدرة على الائتلاف مساهمة كلٍّ من الفعلين الوراثيين التراكمي واللاتراكمي في وراثة تلك الصفات، وبيّنت النسبة (σ2GCA/σ2SCA) أهمّيّة الفعل الوراثي التراكمي في وراثة عدد الحبوب بالصف، وأهميّة الفعل الوراثي اللاتراكمي في وراثة باقي الصفات. أبدت بعض الهجن قوّة هجين إيجابيّة ومعنوية قياساً للشاهد باسل – 1 لجميع الصفات المدروسة عدا صفة ارتفاع النبات. أبدت السلالتان P1 وP5 قدرة عامة جيدة على الائتلاف لصفة غلّة النبات الفردي، وأظهرت الهجن (P2×P8) و(P5×P8) و(P4×P9) و(P1×P7) قدرة خاصة جيدة على الائتلاف لصفة غلّة النبات الفردي، وأشارت نتائج الارتباط المظهري وتحليل المسار إلى ارتباط معنوي موجب لصفة غلة النبات الفردي بكل من صفات طول وقطر العرنوس وعدد الحبوب بالصف ووزن المائة حبة.This study was carried out at the Scientific Agriculture Research Center, Al-Ghab, Syria, during 2013 –2014 growing seasons to estimate heterosis, combining ability, phenotypic correlation and path analysis for plant and ear height, ear length, ear diameter, number of rows per ear, number of kernels per row, 100 kernel weight and grain yield per plant for eighteen hybrids produced by the line × tester method, the major findings were: inbred lines, testers, hybrids and combining ability mean squares were significant for all traits, indicating that additive and non-additive gene actions were the important in inheritance of all traits. The ratios of σ2GCA/σ2SCA showed that non-additive gene action was more important in controlling all traits except of number of kernel per row. Heterosis percentage for all traits were significant compared with the check variety except of ear height trait. GCA effects showed that the lines P1 and P7 were good combiners for grain yield per plant, also, SCA effects showed that P2×P8, P5×P8, P4×P9 and P1×P7 crosses were the best F1 combiners for grain yield per plant. Results of phenotypic correlation and path analysis values showed that ear length, ear diameter and number of kernel per row were positively and significantly associated with grain yield per plant, also, these traits can be considered as selection criteria may lead to the improvement of grain yield in maize.